Summer Thermal Comfort Zoning Studies of Mainland China Based on the Comprehensive Heat Index - Yingfeng Guo; Zhifeng Wu; Zihao Zheng; Xiaojun Huang; Zhongwen Hu (International Journal of Climatology, 2025)
With global warming, a better understanding of the summer thermal environment is crucial. Distinct from land surface temperature, which is the most widely noticed and employed parameter of the summer thermal environment, we constructed the Summer Comprehensive Heat Index using six common heat indices (outdoor apparent temperature, heat index, Humidex, modified discomfort index, net effective temperature, and simplified wet‐bulb global temperature) through principal component analysis, analysing its spatial distribution and temporal trends (2003–2020) at 10 km grid and county scales across mainland China. Employing Automatic Regionalisation with Initial Seed Location, Regionalisation with Dynamically Constrained Agglomerative Clustering and Partitioning, and Spatial Kluster Analysis by Tree Edge Removal regionalisation methods with spatially constrained and classical statistical approaches, a two‐tier geographical division of summer thermal comfort zones was conducted. Results indicate severe thermal stress in Southern China and the Bohai Rim regions, while regions such as the marginal region of the Tibetan Plateau, Inner Mongolia Plateau, and Yungui Plateau offer high thermal comfort, suitable for ‘sunbird’ tourism. Conversely, the Bohai Rim and lower Yangtze regions exhibit extreme heat stress with intensifying warming trends, calling for urgent adaptation. The study highlights regional thermal heterogeneity, providing insights for localised tourism planning and climate resilience strategies.

Large language models for diabetes training: a prospective study - Haoxuan Li; Zehua Jiang; Zhouyu Guan; Yuqian Bao; Yuexing Liu; Tingting Hu; Jiajia Li; Ruhan Liu; Liang Wu; Di Cheng; Hongwei Ji; Yong Wang; et al. (Science Bulletin, 2025)

Toward the bioactive potential of myricitrin in food production: state-of-the-art green extraction and trends in biosynthesis - Yaqian Geng; Yingfeng Xie; Wei Li; Yao Mou; Fang Chen; Jianbo Xiao; Xiaojun Liao; Xiaosong Hu; Junfu Ji; Lingjun Ma (Critical Reviews in Food Science and Nutrition, 2024)

Study on the thermal effect of coal oxidation under different stresses - Jiangkun Chao; Shuang Liu; Rongkun Pan; YingFeng Yuan; Daimin Hu (Science of The Total Environment, 2024)

Study on CO source identification and spontaneous combustion warning concentration in the return corner of working face in shallow buried coal seam - Chengxi Wang; Po Hu; Yingfeng Sun; Chunran Yang (Environmental Science and Pollution Research, 2024)

Integrative taxonomy in a rapid speciation group associated with mating system transition: A case study in the Primula cicutariifolia complex - Wei Zhang; Yingfeng Hu; Siyu Zhang; Jianwen Shao (Molecular Phylogenetics and Evolution, 2023)